Multiple subcutaneous puncture and stoma bag drainage for gross lower limb edema: A case report - Beng, T.S.; Chin, L.E. (Mary Ann Liebert, 2010)
We present a case of gross lower limb edema in a 21-year-old man with an intra-abdominal malignant fibrous histiocytoma. He had a 1-month history of lower limb edema secondary to inferior vena caval obstruction. His edema failed to respond to a combination of diuretics, oral frusemide 40 mg daily and oral spironolactone 100 mg daily. Subcutaneous drainage of both lower limbs with butterfly needles was performed with minimal improvement. However, he gained significant symptomatic relief with multiple subcutaneous punctures and stoma bag drainage. A total of 12.8 L of serous fluid was drained with this simple and effective method. This is the first report of the use of this method.